Monetary aggregation and the p-star model of inflation in Indonesia - Sangeetha Premilla, Dayani. (UNIMAS, 2009)
This study aims to examine an empirical evaluation of the Divisia monetary aggregates that is relative to the traditional simple sum aggregates in Indonesia from 1990:1 to 2005:4. The performance of these aggregates wastested using the Augmented Dickey-Fuller unit root test, Johansen cointegration test and error-correction model. In addition, the information provided by the monetary aggregates as predictors of inflation was examined. Here, the P-Star model of inflation was adapted to examine the performance of the D ivisia monetary aggregates as an information provider in predicting future inflation against the traditional simple sum. The macroeconomic elements that influence inflation in this study includereal GDP, price, interest rate, currency in circulation and money. The results indicate that the Divisia M2 acts as a superior predictor compared to the other monetary aggregates that were used in predicting the future inflation in Indonesia.